The Relationship Between the Intensity of Watching Youtube with Social Emotional Development of Early Children in PAUD Mekar Jaya Lunang Sub-District - Ermawati Ermawati; Syur’aini Syur’aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The background of this research is the high intensity of watching YouTube for early childhood in PAUD Mekar Jaya II, Lunang District, resulting in poor children's social-emotional development. This study aims to (1) describe the intensity of watching YouTube for early childhood at PAUD Mekar Jaya II, Lunang District. (2) Describe the emotional social development of early childhood in PAUD Mekar Jaya II, Lunang District. (3) Seeing that there is no relationship between the intensity of watching YouTube and the emotional social development of early childhood in PAUD Mekar Jaya II, Lunang District. This research is a quantitative type of correlational research that aims to examine the relationship between the independent and dependent variables. The population of this study amounted to 60 children. The samples taken in this study were 45 people/respondents or as much as 75%. The technique used in data collection was in the form of a data collector in the form of a written terminal (questionnaire) and a data collection tool in the form of a list of data collectors. Data analysis techniques use the percentage formula and data processing uses the rank product moment formula. The results of this study prove that: (1) The description of the intensity of watching YouTube for young children in PAUD Mekar Jaya II, Lunang District, is focused on High. (2) The description of the social emotional development of early childhood in PAUD Mekar Jaya II, Lunang District, is in the poor category. (3) There is a significant relationship between the intensity of watching YouTube and the emotional social development of early childhood at PAUD Mekar Jaya II, Lunang District. It is hoped that future researchers can examine new variables so that they can complement and increase the variables in the study.Keywords: Youtube Watching Intensity, Social Emotional Development